STATIC AND DYNAMIC CHARACTERISTICS ANALYSIS AND OPTIMIZATION OF ELECTRIC WHEEL DUMP TRUCK FRAME - MI ChengJi; LI WenTai; NI ZhengShun; XIAO XueWen; YANG QinQuan; XIAO YuePeng; WANG MengLong (Jixie qiangdu, 2020)
In order to analysis static and dynamic characteristics of a certain type electric wheel dump truck frame,the load information of key bearing connection sites of the fame was obtained by the rigid and flexible coupling multi-body dynamics analysis for the whole vehicle and the finite element model of the frame with welding details was constructed simultaneously.Then,the static analysis of the frame on the condition of static state with full load was carried out and its correctness was verified by using stress test on the mine road surface. The dynamic analysis of the frame under the conditions of horizontal bending,ultimate torsion and emergency braking with full load,stiffness analysis and modal analysis were conducted. The results can be illustrated that the stiffness of the frame under the ultimate torsion condition has some room for improvement to avoid frame failure.Therefore,the multi-objective optimization design for the frame stiffness under different conditions was carried out by utilizing topological optimization technology. The result shows that the reconstructed frame after optimization satisfies operating requirements of the whole vehicle and this analysis method also provides some reference experience for frame static and dynamic characteristics design as well.